Dissolved silicon and nitrogen in glacial rivers and water of Blago bay (Russian Arctic, Novaya Zemlya): origin, variability and spreading - G. V. Borisenko; A. A. Polukhin; М. V. Flint (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2023)
Hydrochemical studies of watercourses and the water area of Blagopoluchia bay (Novaya Zemlya, Arctic, Russia) have been carried out. The concentrations of nutrients in rivers and streams are higher than those in the water area of Blagopoluchia bay. It is shown that the concentration of silicon in constantly flowing rivers is 1–13 μM, the concentration of NO3 — 0.5–8, for small and temporary streams these values are higher and are in the range of 18–46 μM Si, 1–11 μM NO3– . The influence of streams and rivers flowing into Blagopoluchia Bay on the water area of the bay is local and extends to 1 km from the mouth, and does not influence the Kara Sea nutrient content. Hydrochemical studies of watercourses and the water area of Blagopoluchia bay (Novaya Zemlya, Arctic, Russia) have been carried out. The concentrations of nutrients in rivers and streams are higher than those in the water area of Blagopoluchia bay. It is shown that the concentration of silicon in constantly flowing rivers is 1–13 μM, the concentration of NO3 — 0.5–8, for small and temporary streams these values are higher and are in the range of 18–46 μM Si, 1–11 μM NO3– . The influence of streams and rivers flowing into Blagopoluchia Bay on the water area of the bay is local and extends to 1 km from the mouth, and does not influence the Kara Sea nutrient content.